Faktor yang Mempengaruhi Keputusan Pembelian Sayuran di Agrowisata Barro Tani Manunggal Desa Kepatihan Kecamatan Selogiri Kabupaten Wonogiri - Desi Listyawati; Rosita Dewati; Yoesti Silvana Arianti; Agung Setyarini (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2023)
Vegetables are one of the most important food sources in supporting a healthy body. The alternative to buy vegetabes is in agrotourism. Barro Tani Manunggal Agrotourism is one of tourism places that provides or sells vegetable commodities. In maintaining agrotourism, it is necessary to know consumer preferences for vegetable products. This study aimed to determine the characteristics of vegetable consumers and the influence factors of consumer preferences for vegetable purchasing decisions at Barro Tani Manunggal Agrotourism. The sampling technique used purposive sampling method. The number of respondents was 56 respondents with the criteria of more than one time bought vegetables in Barro Tani Manunggal Agrotourism. The data analysis methods are t-test, F-test, and coefficient determination. The results show that the average respondent who shopped for vegetable is in aged 15-64 years, most of whom have high schoo or equivalent education. Most of the respondents are entrepreneurs, and the average income of respondents in this study is IDR 2.000.001-3.000.000. The variables of service speed and product availability have a positive and significant effect on purchasing decisions for vegetables in Barro Tani Manunggal Agrotourism. The freshness variable has a negative and significant effect. While the variables of pricing, product quality, location, and convenience do not have a significant effect on vegetable purchasing decisions.